2019
DOI: 10.1177/0898264319894486
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Effects Between Loneliness and Sleep Disturbance in Older Americans

Abstract: Objectives: To model the relationship between loneliness and sleep disturbance over time. Method: Data came from the Health and Retirement Study (2006, 2010, 2014 waves; age ≥ 65 years; n = 5,067). Loneliness was measured via the Hughes Loneliness Scale and sleep disturbance via a four-item scale assessing sleep and restedness. Cross-lagged panel modeling (path analysis) was used to jointly examine reciprocal effects between loneliness and sleep disturbance. Results: Higher loneliness correlated with higher sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 40 publications
(79 reference statements)
3
29
0
4
Order By: Relevance
“…due to abnormal sleep-wake schedule. Dysregulation of the hypothalamic-pituitary-adrenal axis may also be involved (Griffin et al, 2019). Finally, this study demonstrated an association between sleep and depression.…”
Section: Dear Editorsupporting
confidence: 55%
“…due to abnormal sleep-wake schedule. Dysregulation of the hypothalamic-pituitary-adrenal axis may also be involved (Griffin et al, 2019). Finally, this study demonstrated an association between sleep and depression.…”
Section: Dear Editorsupporting
confidence: 55%
“…As such, lack of outdoor activities and physical exercise due to quarantine measures during the COVID-19 pandemic could cause fatigue. Finally, the high mortality rate and poor prognosis of COVID-19 in older adults could lead to perceptions of health risks and psychological distress, which may have resulted in increased loneliness and fatigue [17]. Previous studies found that fatigue was positively associated with female gender and younger age [1,14,23], but these results were based on general samples and assessed under "non-pandemic" conditions.…”
Section: Discussionmentioning
confidence: 96%
“…Anxiety and fear, in addition to provoking a worsening in quality of sleep, increased cortisol levels, reduced melatonin synthesis, with changes in the biological rhythms [31,32]. Also, a dysregulation of the hypothalamic-pituitary-adrenal axis can be involved in the relationship between poor sleep and feelings of loneliness and fear [27,33].…”
Section: Discussionmentioning
confidence: 99%